Análise dos impactos na quebra da cadeia de custódia e o cenário da admissibilidade das provas no processo - Cardoso, Larissa Tammy Patricio Caciano de Souza (2024)
The institute of the chain of custody was introduced into the Brazilian Code of Criminal Procedure with the enactment of Law n. 13.964/2019, known as the “Anti Crime Package”, with the purpose of ensuring the recording and tracking of forensic evidence, from its collection at the crime scene, through the registration of who had access to or handled the evidence, until its eventuais disposal, aiming to guarantee the integrity of the traces of a given crime. The present study aimed to analyze the procedural consequences resulting from the breach or violation of the chain of custody of evidence. Doctrinal discussions on the subject have intensified, resulting in two main currents: one argues that the violation of the chain of custody results in the inadmissibility of the evidence, while the other maintains that the breach only reduces the probative value. This issue is central to the study, as evidence constitutes a fundamental right that must be safeguarded and preserved. Methodologically, this work was developed based on bibliographic research, using books, articles, monographs, dissertations, and theses to achieve the general objective. It is concluded that the breach of the chain of custody hinders the full and effective exercise of the adversarial process by the party that did not have full access to the evidence. Based on the theory of the fruits of the poisonous tree, the contaminated elements become unlawful.